2019
DOI: 10.1016/j.celrep.2019.07.040
|View full text |Cite
|
Sign up to set email alerts
|

SMUG1 Promotes Telomere Maintenance through Telomerase RNA Processing

Abstract: Graphical Abstract Highlights d The SMUG1-DNA glycosylase promotes maturation of the telomeric DNA component, hTERC d SMUG1 regulates the presence of base modifications in hTERC d SMUG1 promotes DKC1 binding and stability of hTERC d hTERC levels limit telomerase activity in human SMUG1knockout cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…We, therefore, concluded that SMUG1 functions in rRNA quality control by regulating the presence of hmU. 4 In our recent study, 6 we showed that SMUG1 is required for maturation of hTERC in human cells by regulating the levels of modified bases located between the CR4-CR5 domain and the H-box, a region important for binding of Dyskerin pseudouridine synthase 1 (DKC1). In the absence of SMUG1, the balance between mature hTERC and its processing intermediates was disturbed.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…We, therefore, concluded that SMUG1 functions in rRNA quality control by regulating the presence of hmU. 4 In our recent study, 6 we showed that SMUG1 is required for maturation of hTERC in human cells by regulating the levels of modified bases located between the CR4-CR5 domain and the H-box, a region important for binding of Dyskerin pseudouridine synthase 1 (DKC1). In the absence of SMUG1, the balance between mature hTERC and its processing intermediates was disturbed.…”
mentioning
confidence: 98%
“…In DNA, SMUG1 initiates Base Excision Repair (BER) of hmU, 5 but SMUG1 also has an RNA-processing function (Figure 1). 4,6 The recognition of RNA modifications by SMUG1 seemed to be coupled to RNA degradation: the accumulation of hmU in rRNA was accompanied by an increase in misprocessed rRNA species targeted for degradation and a reduction in the corresponding mature species. We, therefore, concluded that SMUG1 functions in rRNA quality control by regulating the presence of hmU.…”
mentioning
confidence: 99%
See 3 more Smart Citations